Validating Journal Cancellation Decisions in the Sciences: A Report Card - Andrea L. (Andrea Louise) Duda; Rosemary L. Meszaros (Issues in Science and Technology Librarianship)
Few libraries have remained unaffected by the serials pricing crisis of the past several years. The University of California, Santa Barbara (UCSB) Library has conducted five serials cancellations projects since 1987 -- 1987, 1989, 1991, 1994, and 1996. Each round of cancellations cut closer to the core journals in all of the disciplines. This paper uses almost ten years of interlibrary loan data for statistical and comparative analyses documenting the impact of these cuts.